Analisis Yuridis Mengenai Itikad Buruk dalam Tindak Pidana Penipuan dan Hubungannya dengan Wanprestasi dalam Sengketa Hutang Piutang - Umam, Khairul; Adi, M. Nur Prasetiyo; Pratama, Rizki Yuda; Hidayatullah, Thoriq (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the juridical aspects regarding bad faith related to the element of fraud in the context of accounts payable cases. Default, which is a failure to fulfill a debt payment obligation, often raises the question whether the act can also be considered fraud if it is done in bad faith. The method used in this research is literature study and normative analysis of the relevant laws and regulations, namely the Criminal Code (KUHP) and other regulations related to accounts payable. In this study, the elements of criminal acts of fraud such as deception, use of deception, or falsification of documents will be analyzed in the context of bad faith in default cases. The results of this study indicate that to fulfill the elements of a criminal act of fraud, there is a need to prove that the perpetrator has bad faith, namely the intention to deceive or mislead other parties. However, in the context of default in accounts payable cases, there are considerations that must be considered. One is the difference between inability and unwillingness to pay debts. Impairment caused by valid reasons or difficult economic circumstances cannot be considered as bad faith.